2012
DOI: 10.3109/13561820.2012.720313
|View full text |Cite
|
Sign up to set email alerts
|

Relative distancing: A grounded theory of how learners negotiate the interprofessional

Abstract: Relative Distancing: a grounded theory of how learners negotiate the interprofessional Keywords: IPE, grounded theory, relative distancing, efficiency, identity. AbstractA number of extant educational, psychological and sociological theories have been suggested as possessing utility for interprofessional education (IPE). However, there is limited theory proposed that has been derived directly from data. This article adds to the theoretical toolkit by theorising from data using constructionist grounded theorisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Finally, peer marking (of videos produced by other teams) assisted students in developing evaluative judgement of their team performance compared to that of other teams. Green notes that when ‘students review the work of their peers, they invariably reflect back on their own work and consider ways of improving it…[as] before reviewing the work of peers, students will have already spent considerable time producing work in the same domain topic themselves’ [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, peer marking (of videos produced by other teams) assisted students in developing evaluative judgement of their team performance compared to that of other teams. Green notes that when ‘students review the work of their peers, they invariably reflect back on their own work and consider ways of improving it…[as] before reviewing the work of peers, students will have already spent considerable time producing work in the same domain topic themselves’ [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative free text data from the questionnaire was analysed thematically [ 42 ]. Two researchers experienced in qualitative research (CJ and GN) undertook the initial analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Within the higher education arena, peer assessment is a recognised learning and teaching strategy to develop student skills in giving and receiving feedback, reflective practice and accountability for personal learning [ 39 41 ]. Because students have spent considerable time producing their own work, when assessing others’ work within the same topic area, they begin to compare and contrast both pieces of work, invariably noting ways in which their own work could be improved [ 42 ], aiding student self-assessment and reflection [ 43 ]. Stone [ 44 ] suggested that peer assessment, in the context of IPL encourages cooperative learning, and should be weighted accordingly to signify its importance in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, attitudes and stereotypes with respect to colleagues in one’s own profession or in other professional groups are looked on as important factors for the success of teamwork [8]. The attitude towards interprofessional learning represents a prerequisite that promotes learning achievement and the development of one’s own professional identity as opposed to the other professions in the team [9], [10]. …”
Section: Introductionmentioning
confidence: 99%